2007
DOI: 10.3171/jns-07/07/0094
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus organization and healing in the swine experimental aneurysm model. Part I. A histological and molecular analysis

Abstract: This investigation provides a detailed histological and molecular analysis of thrombus organization in the swine aneurysm model. The companion study will describe the effect of embolic bioabsorbable polymers on this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 54 publications
8
35
0
1
Order By: Relevance
“…9,13,35,54,55 Early inflammatory changes 39,54,55 were followed by a centripetal myofibroblast infiltration, robust collagen deposition, and a thick neointima, which completely sealed the neck. 48 When all specimens showed permanent occlusions and favorable healing characteristics at some delayed time points, as seen in swine aneurysms, then some earlier timeframe was chosen, in hopes of detecting accelerated healing with some new material.…”
Section: Pathologic Analyses Of Treated Aneurysmsmentioning
confidence: 99%
“…9,13,35,54,55 Early inflammatory changes 39,54,55 were followed by a centripetal myofibroblast infiltration, robust collagen deposition, and a thick neointima, which completely sealed the neck. 48 When all specimens showed permanent occlusions and favorable healing characteristics at some delayed time points, as seen in swine aneurysms, then some earlier timeframe was chosen, in hopes of detecting accelerated healing with some new material.…”
Section: Pathologic Analyses Of Treated Aneurysmsmentioning
confidence: 99%
“…Results of previous studies already demonstrated the paramount importance of aneurysm wall smooth muscle cells in thrombus organization and neointima formation. 6,19 Therefore, it can be hypothesized that loss of mural cells is causative for the failure of luminal thrombus transformation into stable fibrotic tissue.…”
Section: Luminal Thrombus Formationmentioning
confidence: 99%
“…11,19,25 They are not currently considered appropriate for this purpose because of their propensity for thrombosis and complete closure of aneurysmal necks with thick neointima formation in all animals at 1 month, no matter what material is used. Reports of experimental aneurysms in other species (eg, canines and rabbits) have demonstrated a much greater incidence of long-term patency and a lower incidence of spontaneous hemorrhage (essentially 0) than were observed in our study.…”
Section: Aspect Ratio and Giant Aneurysm Modelmentioning
confidence: 99%
“…Our findings suggest that thrombosis is accompanied by degeneration of the aneurysm wall, as found in other experimental or human aortic aneurysms. [9][10][11][12] Inflammation of the venous wall was present in unruptured and in ruptured cases. In our model, the distinguishing factor was the presence of recanalization between the thrombus and the necrosing wall.…”
Section: Thrombosis Followed By Rupturesmentioning
confidence: 99%
See 1 more Smart Citation